Monoterpenoid indole alkaloids and phenols are required antioxidants in glutathione depleted Uncaria tomentosa root cultures - Vera-Reyes, Ileana; Huerta-Heredia, Ariana A.; Ponce-Noyola, Teresa; Cerda-García-Rojas, Carlos M.; Trejo-Tapia, Gabriela; Ramos-Valdivia, Ana C. (Frontiers in Environmental Science, 2015)
Plants cells sense their environment through oxidative signaling responses and make appropriate adjustments to gene expression, physiology and metabolic defense. Root cultures of Uncaria tomentosa, a native plant of the Amazon rainforest, were exposed to stressful conditions by combined addition of the glutathione inhibitor, buthionine sulfoximine (0.8 mM) and 0.2 mM jasmonic acid. This procedure induced a synchronized two-fold increase of hydrogen peroxide and guaiacol peroxidases, while the glutathione content and glutathione reductase activity were reduced. Likewise, in elicited cultures, production of the antioxidant secondary metabolites, monoterpenoid oxindole, and glucoindole alkaloids, were 2.1 and 5.5-fold stimulated (704.0 ± 14.9 and 845.5 ± 13.0 μg/g DW, respectively) after 12 h, while phenols were three times increased. Upon elicitation, the activities and mRNA transcript levels of two enzymes involved in the alkaloid biosynthesis, strictosidine synthase and strictosidine β-glucosidase, were also enhanced. Differential proteome analysis performed by two-dimensional polyacrylamide gel electrophoresis of elicited and control root cultures showed that after elicitation several new protein spots appeared. Two of them were identified as thiol-related enzymes, namely cysteine synthase and methionine synthase. Proteins associated with antioxidant and stress responses, including two strictosidine synthase isoforms, were identified as well, together with others as caffeic acid O-methyltransferase. Our results propose that in U. tomentosa roots a signaling network involving hydrogen peroxide and jasmonate derivatives coordinately regulates the antioxidant response and secondary metabolic defense via transcriptional and protein activation.